ANALYZING THE ISLAMIC BOARDING SCHOOL ENVIRONMENT IN INCREASING THE INDEPENDENCE OF DARULUGGAH WALKAROMAH STUDENTS - David Byrne; Benny Hamdani; Rofiqi Amfatwa (Universitas Islam Zainul Hasan Genggong, 2023)
Santri are students who live in boarding schools. In general, students live with all their independence without the services of parents as at home. This research was conducted at Pondok Darullugah Walkaromah. The approach used is a qualitative approach using descriptive analysis with the intention of describing events, people's behavior or a situation in the form of a narrative, to foster the independence of students, examples and diligence are needed for ustad or ustdah to provide direction for students so that students can adapt to the pesantren environment and have an independent attitude.